Patterns and clinical significance of non-specific myocardial fibrosis; Evidence from a cohort of young competitive athletes referred to a tertiary referral centre. (11th May 2022) - Androulakis, E; Papatheodorou, S; Merghani, A; Sharma, S; Papadakis, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Non-specific myocardial fibrosis (NSMF) is a heterogeneous entity whose clinical significance remains unknown. Purpose: We aimed to evaluate a cohort of young competitive athletes with and without NSMF to establish potentially clinically significance. Methods: We analysed data from 328 young athletic individuals referred to our dedicated Sports Cardiology service for a variety of reasons. All athletes underwent an evaluation with 12-lead ECG, Holter, cardiopulmonary exercise test (CPET) and cardiac magnetic resonance (CMR). After excluding individuals with NSMF due to a well-defined cardiac condition, we identified 60 athletes with NSMF (80% male, 72% white, 65% endurance sport) and compared them with a similar group of 75 athletes no fibrosis. Athletes with NSMF were further divided into Group 1 (n=32) with minimal ('minor') fibrosis and Group 2 (n=28), with more extended/non-focal ('major') fibrosis. Athletes were followed-up for adverse events, including supraventricular and ventricular tachycardia (VT), cardiac symptoms leading to A/E presentations and hospital admissions. Results: Hours of exercise, baseline heart rate, cardiac volumes, function and CPET performance were similar between the two groups. Athletes with NSMF demonstrated a higher prevalence of lateral T-wave inversion (48 vs. 17%, p<0.001) and ventricular arrhythmias (VEs>500/24h 13.1 vs 2.6%, p=0.046; non-sustained ventricular tachycardia 5.2% vs 0%) compared to athletes without NSMF. Regarding fibrosis localization, 28.6% of the NSMF group had mid-wall, 16.1% subepicardial and 7.1% subendocardial patterns respectively. Athletes of black ethnicity were more likely to have a subepicardial pattern (OR: 5, CI; 1.45-16.67, p=0.004) and those with lateral T-wave inversion (OR: 5.40, CI; 1.70-17.10, p=0.004) were more likely to exhibit major NSMF. In contrast, athletes with minor NSMF had higher right ventricular end diastolic (RVEDV) volumes (104.2±3.6 vs 86.9±5.3 mL/m2, p=0.008) and demonstrated higher values of maximum heart rate (182±13 vs 171±15 bpm, p=0.016), maximum Watts (328.5±18.5 vs 259.2±8.2, p=0.017) and maximum oxygen uptake (V02) (p=0.003), compared to athletes with major NSMF. After adjustment for confounders, the presence of lateral T-wave inversion (p=0.026) and a maximum <44 mL/min/Kg (p=0.040) remained the only significant predictors for presence of major NSMF. During 45.5±25.1 months of follow up, 20 adverse events occurred. No athlete exhibited cardiac arrest or death. Cox regression analysis revealed athletes with major fibrosis were 9.1 more likely to exhibit an adverse event (CI; 1.1-76.3, p=0.041). Conclusions: The presence of lateral T-wave inversions is associated with increased risk of myocardial fibrosis and should prompt comprehensive evaluation with a cardiac MRI. Major fibrosis was associated with increased prevalence of arrhythmias and adverse events, highlighting the importance of close monitoring and long-term follow-up.